Primary perianal alveolar rhabdomyosarcoma with uncommon metastatic sites: a case report and follow-up using 18F-FDG PET/CT - Yang, Yihan; Chen, Zhao; Qiu, Yongkang; Cheng, Jia; Na, Ritai; Liu, Min; Kang, Lei (Frontiers in Medicine, 2024)
Background Rhabdomyosarcoma (RMS), a rare pediatric soft tissue neoplasm, predominantly develops in late childhood and adolescence with no discernible gender bias. Alveolar rhabdomyosarcoma (ARMS) stems from mesenchymal cells and may develop most frequently in the trunk, extremities, and head/neck areas, while occurrences in the pelvic cavity are less frequent. The manifestation is typically characterized by a high rate of aggressive metastasis and a poor overall survival prognosis. Case report We present the case of an 11-year-old girl with ARMS initially presenting with a perianal mass. The diagnostic workup included MRI and PET/CT, which highlighted the tumor’s aggressive nature and metastatic potential. Subsequent metastases to the pleura, lymph nodes, and, less frequently, to the bone were detected using 2-deoxy-2-[fluorine-18]-fluoro-D-glucose positron emission tomography combined with computed tomography (18F-FDG PET/CT) imaging. The patient underwent a multi-regimen chemotherapy protocol but showed an incomplete response, indicating a poor prognosis. Conclusion This report presents a rare case of ARMS primarily located in the perianal region with multiple metastases, including the uncommon occurrence of bone metastasis, which illustrates the challenges in diagnosing and treating ARMS, emphasizing the need for accurate and early diagnosis, advanced imaging for disease assessment, and more effective treatment strategies. 18F-FDG PET/CT imaging highlights its preeminence in detecting multiple rare metastatic lesions. However, the persistent disease activity despite treatment highlights the need for further research into the biology of ARMS and the development of novel therapeutics to improve patient outcomes.